2002
DOI: 10.1139/y02-135
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal brain amines in methotrexate-induced learning and memory deficit

Abstract: Intrathecal methotrexate in children with leukemia is known to cause seizures, dementia, leukoencephalopathy, and cognitive dysfunction after long-term treatment. To investigate the cognitive dysfunction, male Wistar rats were given multiple intracerebroventricular injections of methotrexate. Its effect on behaviour was tested in the two-compartment conditioned avoidance task and dark-bright arena test. Levels of brain amines in the hippocampal region of the brain were estimated by HPLC. The qualitative and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 40 publications
5
54
0
3
Order By: Relevance
“…Although evaluation at a 3-year timepoint following treatment was not conclusive, the reduced volumes at 1 year significantly correlated with poor performance measures of attention and visual memory. Gray and white matter volume loss and hippocampal atrophy following chemotherapy have also been reported by other groups [39,48,49]. Baehring and Fulbright described a delayed leukoencephalopathy syndrome with distinct diffusion-weighted imaging abnormalities on MRI indicative of toxic white matter damage.…”
Section: Neuroimaging Studies In Patients Treated With Chemotherapysupporting
confidence: 66%
“…Although evaluation at a 3-year timepoint following treatment was not conclusive, the reduced volumes at 1 year significantly correlated with poor performance measures of attention and visual memory. Gray and white matter volume loss and hippocampal atrophy following chemotherapy have also been reported by other groups [39,48,49]. Baehring and Fulbright described a delayed leukoencephalopathy syndrome with distinct diffusion-weighted imaging abnormalities on MRI indicative of toxic white matter damage.…”
Section: Neuroimaging Studies In Patients Treated With Chemotherapysupporting
confidence: 66%
“…In previous studies, these doses of methotrexate alone disrupted conditioned taste aversion, conditioned emotional responses, spatial memory, and novel object recognition (Madhyastha et al 2002;Seigers et al 2008;Yanovski et al 1989) but failed to alter responding in a different conditioned taste aversion assay and a Pavlovian appetitive conditioning assay (Stock et al 1995). The doses of 3.2-32 mg/kg methotrexate used in mice and rats fall within the predicted 8-42-mg/kg-scaled mouse doses as determined from the range of clinical doses used to treat breast cancer in humans (40 mg/m 2 ) according to pharmacokinetic studies (Lobo and Balthasar 2003;Ohdo et al 1997;Peters et al 1993).…”
Section: Discussionmentioning
confidence: 81%
“…Methylscopolamine, a muscarinic acetylcholine antagonist similar to scopolamine but with limited capacity to cross the blood-brain barrier and exert central nervous system effects, can be used to assess the peripheral contributions of muscarinic blockade to learning and memory deficits (Richmond et al 1997;Shannon and Eberle 2006). The doses of methotrexate and 5-fluorouracil examined in the present autoshaping-operant procedure were similar to the doses examined in other preclinical rodent studies using spatial learning, conditioned taste aversion, and conditioned avoidance or fear tasks (Lee et al 2006;Madhyastha et al 2002;Stock et al 1995;Winocur et al 2006;Yanovski et al 1989). …”
mentioning
confidence: 72%
“…Madhyastha et al found a learning and memory impairment, but no anxiolytic effects in the two-compartment conditioned avoidance task after multiple intracerebroventricular injections of MTX in Wistar rats [27]. Sieklucka-Dziuba et al reported an impairment of long-term memory in the passive avoidance task 14 days after a single dosage of MTX injected intraperitoneal in Albino Swiss mice [40].…”
Section: Discussionmentioning
confidence: 99%